Rajasthan’s Ecosystem for Social Innovations and Social Entrepreneurship: Preliminary Study Among Academic Leaders of Rajasthan - Jain, Dr. Trilok Kumar (Journal of Advanced Research in Entrepreneurship, Innovation and SMES Management, 2026)
Rajasthan is a state which has huge potential for the development of social innovations and social entrepreneurship considering The legacy and its heritage, however, the initiatives and directions towards social innovations and social entrepreneurship need a careful and detailed study. This study is a preliminary study to identify the overall perspective with regard to social innovations and social entrepreneurship. Interviews of 50 academic leaders were conducted to identify the direction and the magnitude of social innovations and socialise the need for a renewed focus on social innovations and social The government of Rajasthan should take up detailed studies and should foster social innovations and social entrepreneurship and institutions for these calls and promote social innovations and social More detailed study would be required to identify the direction and magnitude of efforts for posting social innovations and social entrepreneurship.